Women in charge - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
For women to gain access to resources and have a say in their own destinies continues to be a major challenge. In the Mozambican districts of Tete and Changara, female-headed households have taken things into their own hands, forming groups to...